2019
DOI: 10.1097/pas.0000000000001385
|View full text |Cite
|
Sign up to set email alerts
|

Flat Epithelial Atypia in Breast Core Needle Biopsies With Radiologic-Pathologic Concordance

Abstract: Flat epithelial atypia (FEA) is an alteration of terminal duct-lobular units by a proliferation of ductal epithelium with low grade atypia. No consensus exists on whether the diagnosis of FEA in core needle biopsy (CNB) requires excision (EXC). We retrospectively identified all in-house CNBs obtained between 1/2012-7/2018 with FEA. We reviewed all CNB slides and assessed radiologic-pathologic concordance. An upgrade was defined as invasive carcinoma (IC) and/or ductal carcinoma in situ in the EXC. The EXC slid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…Historically, excisional biopsy has been recommended after a core needle biopsy diagnosis of all high risk lesions. Recent data suggest that upgrade rates to carcinoma in situ or invasive carcinoma are 4-23% for lobular neoplasia [27,28], up to 29% for ADH [18], 3-5% for flat epithelial atypia [29,30], 2-6% for papilloma without atypia [31][32][33], and 2-28% for radial scar [34] [35]. Most of these studies found that…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Historically, excisional biopsy has been recommended after a core needle biopsy diagnosis of all high risk lesions. Recent data suggest that upgrade rates to carcinoma in situ or invasive carcinoma are 4-23% for lobular neoplasia [27,28], up to 29% for ADH [18], 3-5% for flat epithelial atypia [29,30], 2-6% for papilloma without atypia [31][32][33], and 2-28% for radial scar [34] [35]. Most of these studies found that…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…CCLs are most frequently identified in CNBs performed for mammographically detected calcifications. While the majority of CCLs manifest as grouped amorphous calcifications, fine pleomorphic or punctate calcifications can also be observed [ 2 , 3 , 6 , 8 , 9 , 10 , 32 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The calcifications associated with CCLs may be indistinguishable from other causes of suspicious calcifications such as ADH or DCIS, necessitating biopsy or excision for diagnosis [ 2 ].…”
Section: Radiologic Findingsmentioning
confidence: 99%
“…Sonographically, CCLs with and without atypia may present as cystic or solid lesions as well as a mass with irregular, microlobulated or indistinct borders and hypoechoic or complex echotexture [ 2 , 38 , 39 , 43 , 45 , 46 ]. There are no reported specific mammographic or ultrasound features which aid in the distinction of patients with CCLs with or without atypia [ 2 , 45 ].…”
Section: Radiologic Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, CCLs, including columnar cell hyperplasia, have similar neoplastic genetic alterations [30,31]. At present, CCL cases need to be followed up closely [32][33][34]. Therefore, distinguishing CCLs from normal mammary glands is important for breast biopsy tissue.…”
Section: Experiments 3: Ccls Vs Normal Distinguishing Ccls and Normal Mammary Glandsmentioning
confidence: 99%